Early Neonatal Pain—A Review of Clinical and Experimental Implications on Painful Conditions Later in Life - Williams, Morika D.; Lascelles, B. Duncan X. (Frontiers in Pediatrics, 2020)
Modern health care has brought our society innumerable benefits but has also introduced the experience of pain very early in life. For example, it is now routine care for newborns to receive various injections or have blood drawn within twenty-four hours of life. For infants who are sick or premature, the pain experiences inherent in the required medical care are frequent and often severe, with neonates requiring intensive care admission encountering approximately fourteen painful procedures daily in the hospital. Given that much of the world has seen a steady increase in preterm births for the last several decades, an ever-growing number of babies experience multiple painful events before even leaving the hospital. These noxious events occur during a critical period of neurodevelopment when the nervous system is very vulnerable due to immaturity and neuroplasticity. Here, we provide a narrative review of the literature pertaining to the idea that early life pain has significant long-term effects on neurosensory, cognition, behavior, pain processing, and health outcomes that persist into childhood and even adulthood. We refer to clinical and pre-clinical studies investigating how early life pain impacts acute pain later in life, focusing on animal model correlates that have been used to better understand this relationship. Current knowledge around the proposed underlying mechanisms responsible for the long-lasting consequences of neonatal pain, its neurobiological and behavioral effects, and its influence on later pain states are discussed. We conclude by highlighting that another important consequence of early life pain may be the impact it has on later chronic pain states – an area of research that has received little attention.